IMPROVING STUDENTS’ THINKING ABILITY IN PHYSICS USING INTERACTIVE MULTIMEDIA BASED PROBLEM SOLVING - Sondang R Manurung; Deo Demonta Panggabean (LPMPP Universitas Negeri Yogyakarta, 2020)
Interactive multimedia based learning containing problem solving may have been researched, however there are stigma that learning how to do problem solving conventionally particularly for colleague students is still favorable. The purpose of this paper is to evaluate factors affect the student learning outcomes. The independent variable is a teaching method in the form of interactive multimedia based on problem solving (IMM-PS) and the dependent variable is students' thinking ability in physics. Specifically, this study aims to analyze the problem solving abilities of students in physics education programs after they have been exposed to interactive multimedia based problem solving methods. The research type is quasi-experiment. The sample were second year physics education students who studying wave electric magnetic subjects, as many as seventy students. The test of science process skills in the form of formal descriptions as well as reasoning tests in the form of descriptions were used as instruments for this study. The results show that the problem solving ability of students who study physics using interactive multi-media based problem solving is better than students who learn through conventional methods.